2001
DOI: 10.1063/1.1427755
|View full text |Cite
|
Sign up to set email alerts
|

Field emission characteristics of BN/GaN structure

Abstract: n -type gallium nitride (GaN) layers grown on sapphire substrates by metalorganic chemical vapor deposition are used to examine field emission characteristics. The electron concentration of the GaN is 2×1017 cm−3. In order to enhance the electric field, the GaN surface is roughened by hydrogen (H2) plasma treatment. Boron nitride (BN) films are grown on the roughened surface of the GaN by plasma-assisted chemical vapor deposition. The turn-on electric field between the anode and sample surface is estimated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…4 that the current density of high cubic phase BN is about 100 times greater than that of pure h-BN. Kimura et al [8] suggested that the greater current density of high cubic phase BN was due to the larger area of its emitted surface. However, our results show that the surface morphology of c-BN is similar to that of h-BN.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…4 that the current density of high cubic phase BN is about 100 times greater than that of pure h-BN. Kimura et al [8] suggested that the greater current density of high cubic phase BN was due to the larger area of its emitted surface. However, our results show that the surface morphology of c-BN is similar to that of h-BN.…”
Section: Article In Pressmentioning
confidence: 99%
“…Moreover, the possibility of synthesizing c-BN/Si heterostructures and the high thermal and chemical stability further make it one of heated candidates for field emission cathode materials. Recently, there have been some reports on field emission characteristics of c-BN films [5][6][7][8][9], which all demonstrated that c-BN coating was significantly effective in enhancing emission current operation. These experiments also showed that the field emission properties of BN films constructed by different phase formation are remarkably distinct.…”
Section: Introductionmentioning
confidence: 98%
“…In x Ga 1Àx N, however, has very nice oxidation durability. Though numerous studies, such as photoluminescence (PL) properties [9][10][11], electron transport properties [12], phase separation [13] and impurity doping characteristics [14][15][16] of ternary In x Ga 1Àx N alloy have been reported, and there have been several reports on FEE of GaN [17][18][19][20] to our knowledge, there have been no reports on the FEE properties of InGaN nanowires. If InGaN materials with good FEE can be prepared, the integration of optoelectronic devices and microelectronic devices can be achieved.…”
Section: Introductionmentioning
confidence: 96%
“…[8][9][10] Metal oxide materials such as indium, tin, molybdenum, and chromium oxides have stimulated considerable attention in recent years as promising cold-cathode coating materials due to their remarkable physical and chemical stability during the emission process. 11,12 In our previous experiment, 13 wide-band-gap material ͑WBGM͒-coated CNTs ͑such as MgO or SiO 2 -coated CNTs͒ gave excellent emission characteristics, and the emission stability was not affected after exposure to oxygen molecules which were regarded as a critical FE current degradation source. 14 The other important coating material we suggest here is indium oxide.…”
Section: Introductionmentioning
confidence: 99%